2019
DOI: 10.1002/1438-390x.12003
|View full text |Cite
|
Sign up to set email alerts
|

Abundance decline in the narrow‐ridged finless porpoise population off the Pacific coast of eastern Japan

Abstract: The narrow-ridged finless porpoise Neophocaena asiaeorientalis is a small-toothed whale with a coastal habitat and is sensitive to human activity. Aerial sighting surveys were conducted in 2012 to evaluate the abundance and distribution of the Sendai Bay-Tokyo Bay population off the Pacific coast of eastern Japan. We flew along 35 east-west transects at intervals of 11.6 km over the study area between 34 57 0 and 38 21' N. In total, 25 groups were detected by two observers. The mean group size was 1.44 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…km −2 in the eastern Shandong Peninsula [31]. These densities were much lower than those estimated in western Korean waters [10] and Japanese waters [48][49][50][51]. Given the relatively low density of porpoise populations along the Shandong Peninsula and the increasing trend of incidents, conservation efforts for porpoises in this area are necessary.…”
Section: Conservation and Managementmentioning
confidence: 86%
“…km −2 in the eastern Shandong Peninsula [31]. These densities were much lower than those estimated in western Korean waters [10] and Japanese waters [48][49][50][51]. Given the relatively low density of porpoise populations along the Shandong Peninsula and the increasing trend of incidents, conservation efforts for porpoises in this area are necessary.…”
Section: Conservation and Managementmentioning
confidence: 86%
“…Identifying critical habitats for this species is notably difficult due to their small size, shy nature and wide‐ranging mobility. Since 2007, only a few opportunistic surveys have been conducted throughout this species' range (Choi et al, 2021; Li et al, 2023; Park et al, 2015; Shirakihara et al, 2019). As effective conservation planning relies on robust baseline data (Huang, 2022; Kiani et al, 2023), the following actions are highly recommended to resolve the current data deficiency. At the initial stages of research into the East Asian finless porpoise, applying local ecological knowledge (LEK) and stranding reporting schemes can be highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…This change reflects alarming population declines observed across their range, including a 70% decrease in areas like the Seto Inland Sea and the South Korean Yellow Sea, signalling a dire need for action (e.g. Park et al, 2015;Shirakihara et al, 2007;Shirakihara et al, 2019). While research on baseline data has increased, most studies focus on Japanese and Korean waters (Choi et al, 2021;Park et al, 2017Park et al, , 2018Shirakihara et al, 2019), with limited data from coastal China (Wang & Reeves, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows how the 2011 tsunamis damaged marine vegetation across a large coastal area. Shirakihara et al (2019) provided evidence that the abundance of the narrow-ridged finless porpoise (Sunameri in Japanese) off the Pacific coast from Tokyo Bay to Sendai Bay declined from 2000 to 2012 and suggested that the 2011 tsunamis caused this decline. They also cautioned the possibility that, although the tsunamis' impact was a temporary event, the abundance of this porpoise species may continue to decline in the future due to human-induced threats such as fisheries bycatch.…”
mentioning
confidence: 99%